HUKUM EKONOMI DARI SUDUT CRITICAL LEGAL STUDIES - Harniwati, Harniwati (Ensiklopedia of Journal, 2023)
The main ideas of critical legal studies are the law seeking wrong legitimacy; Shackled by contradictions; There are no basic Principles in law; and Law is not neutral. The development of critical legal studies is used to understand oppressive legal policies and structures. Another advantage of critical legal studies is the great attention it pays to the recognition of the individual as the main subject of will in the social order. The weakness of the original nature of critical thinking is that it always deconstructs itself so that changes and fluctuations always occur. It is hoped that the idea of critical legal studies will be maximally applied in Indonesia as a jack of all trades in law enforcement in Indonesia. Thoughts about critical legal studies are expected to be used by law enforcers in Indonesia in solving legal problems that are being faced.